A method to control terpineol production from turpentine by acid catalysts mixing. Issue 10 (October 2020) - Prakoso, Tirto; Putra, Ilham Ardiyanto; Handojo, Lienda; Soerawidjaja, Tatang Hernas; Winoto, Haryo Pandu; Indarto, Antonius
Abstract: Terpineol, a promising valorisation product of pine industry, is widely used as an active ingredient for disinfectant soap, cleansers, perfumes, and pharmaceutical purposes. Synthesis of terpineol is generally carried out by separation of α-pinene compounds from crude turpentine through fractionation and then hydrated (addition of water) with the help of acid catalysts. However, direct turpentine hydration without pre-fractionation process can be more beneficial from economic and process point of views. This study aims to investigate the effect of both single and mixed/combined catalysts towards terpineol yield. Combined strong and weak acid catalysts were required to obtain high feed conversion and terpineol yield. The selectivity of terpineol is then correlated to the solubility of a weak/organic acid. In this study, the highest yield of terpineol was 54.0 ± 8.2%-w/w using combination of formic acid and sulphuric acid. Abstract : Chemical engineering; Natural product chemistry; Catalyst; Chemical reaction engineering; Industrial chemistry; Chemical synthesis; Turpentine; Terpineol; Hydration reaction; Acid catalysts.